2013
DOI: 10.1136/bmjqs-2013-001828
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the complexity of medication safety using a human factors approach: an observational study in two intensive care units

Abstract: Objective To examine medication safety in two ICUs and to assess the complexity of medication errors and adverse drug events (ADEs) in ICUs across the stages of the medication-management process. Methods Four trained nurse data collectors gathered data on medication errors and ADEs between October 2006 and March 2007. Patient care documents (e.g., medication order sheets, notes) and incident reports were used to identify medication errors and ADEs in a 24-bed adult medical/surgical ICU and an 18-bed cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 25 publications
3
87
0
1
Order By: Relevance
“…In one study, Rothschild et al (2005) found medications were responsible for 78% of serious errors in the ICU. Reported rates of ICU medication-related errors that either caused patient harm (i.e., preventable adverse drug events [ADEs]) or had the potential to cause patient harm (i.e., near misses) range from 9.2 to 12.8 per 1,000 patient-days and 116.8 to 276 per 1,000 patient-days, respectively (Carayon et al, 2014; Rothschild et al, 2005). Carayon et al (2014) found an average of 2.9 preventable or potential ADEs per ICU patient admission.…”
Section: Facilitated Nurse Medication-related Event Reporting To Imprmentioning
confidence: 99%
“…In one study, Rothschild et al (2005) found medications were responsible for 78% of serious errors in the ICU. Reported rates of ICU medication-related errors that either caused patient harm (i.e., preventable adverse drug events [ADEs]) or had the potential to cause patient harm (i.e., near misses) range from 9.2 to 12.8 per 1,000 patient-days and 116.8 to 276 per 1,000 patient-days, respectively (Carayon et al, 2014; Rothschild et al, 2005). Carayon et al (2014) found an average of 2.9 preventable or potential ADEs per ICU patient admission.…”
Section: Facilitated Nurse Medication-related Event Reporting To Imprmentioning
confidence: 99%
“…medication errors and adverse drug events or ADEs) was based on the protocol of Bates and colleagues [26] and has been described in a previous publication [15]. We categorized medication safety events into:…”
Section: Methodsmentioning
confidence: 99%
“…Various patient safety researchers have employed concepts from human factors to study safety issues in healthcare settings. 2325 …”
Section: Conceptual Frameworkmentioning
confidence: 99%